The Surface Plasmon Polaritons at the Metal which is Sandwiched between Two Different Dielectrics (Dielectric 1/ Metal/ Dielectric 2) (International Journal of Scientific Research and Management (IJSRM), 2025)
Electromagnetic waves that propagated at the interface between metal and dielectrics were widely known as surface plasmon polaritons (SPP). This type of polaritons attracted many people to study since the frequency was in the terahertz region. Hence, it can be utilized in the terahertz technology. The properties of polaritons were represented by dispersion relation. The method to derive the formulation of surface polaritons was by solving Maxwell’s equations, then it was followed by analyzing continuity of the fields at the involved interfaces. The derived dispersion relation was solved numerically using finding root technique. In this study, we analyze SPP in dielectric 1 / metal / dielectric 2 geometry. Here, dielectric 1 and dielectric 2 were differetnt dielectrics with the different values of permittivity. It was found that the dispersion relation curve of SPP consisted of two branches. One branch represented SPP that was generated and propagated at the top surface. The other branch was SPP at the bottom surface of metal film. We also found if the usage of two different dielectrics with the different values of permittivities were large, then difference of the two curves were also significant.